Complete remission of multiple liver metastases with only partial response of the primary rectal cancer after neoadjuvant chemotherapy - Satomi Miura; Kyoji Ito; Nobuyuki Takemura; Fuminori Mihara; Tomomichi Kiyomatsu; Norihiro Kokudo (Surgical Case Reports)
Abstract Background Colorectal cancer is commonly diagnosed among the Japanese population, and various strategies in treating the colorectal liver metastasis have been introduced over the years. Here, we present a case of colorectal liver metastases in which we devised a multidisciplinary treatment plan for a better prognosis. Case presentation We report a case of a 44-year-old female who developed rectal cancer with advanced synchronous liver metastases and was treated by a liver-first surgical approach following neoadjuvant chemotherapy. At diagnosis, there were 12 bilobular lesions in the liver, and the primary rectal cancer was asymptomatic and unprogressive. We adopted a liver-first strategy because the control of the liver metastases was considered the key prognostic factor. Furthermore, because the lesions were highly progressive, we planned neoadjuvant systemic chemotherapy first to provide an observational period to identify potential new metastatic lesions that were refractory to systemic chemotherapy or contraindicative for surgical resection. We administered two courses of S-1 + oxaliplatin (SOX)+ bevacizumab (BV) and an additional course of SOX without BV as neoadjuvant chemotherapy in preparation for surgery. This resulted in a prominent minimalization of colorectal liver metastases, and no other remote metastasis was observed. Then, surgical resection of the colorectal liver metastases was performed safely, and the pathological result revealed complete remission of all tumors by neoadjuvant chemotherapy. The primary tumor in the colon was successfully resected 2 months after the hepatectomy. Although the patient experienced a recurrence in two different sites in the lungs 10 months after resection of the primary rectal lesion, these metastases were successfully resected after diagnosis. The patient is alive with no signs of recurrence 3 years after the diagnosis of colorectal cancer with synchronous liver metastases. Conclusions The combination of a liver-first strategy and neoadjuvant chemotherapy is a possible treatment of choice to cure colorectal cancer with simultaneous advanced colorectal liver metastases.